2006
DOI: 10.1038/sj.jhh.1002104
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and blood pressure across three populations in Africa and Asia

Abstract: Despite a growing burden of obesity and hypertension in developing countries, there is limited information on the contribution of body mass index (BMI) to blood pressure (BP) in these populations. This study examines the association between BMI and BP in three populations across Africa and Asia. Data on BMI, BP and other background characteristics of study participants were generated using the World Health Organization STEPwise approach to surveillance (STEPS), at three demographic surveillance sites in Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

41
169
11
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(236 citation statements)
references
References 43 publications
41
169
11
9
Order By: Relevance
“…Analysis of the relationship between blood pressure and BMI that has been disaggregated into underweight, normal BMI and overweight (or obese) has not always yielded a positive association. Related to this, Tesfaye et al 2 described a J-shaped relationship between BMI and blood pressures, an observation which has been suggested before, although inconsistently. 9 In addition, some researchers have described a minimum threshold required for BMI to be positively associated with blood pressure.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Analysis of the relationship between blood pressure and BMI that has been disaggregated into underweight, normal BMI and overweight (or obese) has not always yielded a positive association. Related to this, Tesfaye et al 2 described a J-shaped relationship between BMI and blood pressures, an observation which has been suggested before, although inconsistently. 9 In addition, some researchers have described a minimum threshold required for BMI to be positively associated with blood pressure.…”
mentioning
confidence: 85%
“…The study by Tesfaye et al 2 also reported higher blood pressures in men than in women a phenomenon sometimes referred to as gender dichotomy in blood pressure, which is universal in Caucasianbased studies. 1 Some studies have reported higher blood pressures and hypertension prevalence rates among women than men, an observation which may appropriately be called 'reversed gender dichotomy' in blood pressure.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Many low to middle income countries also show increasing levels of male-led incidence in regions like Eastern and Central Europe, particularly in Hungary, Poland and Serbia (WHO-IARC, 2014;Lortet-Tieulent et al, 2014;Tesfaye et al, 2007). A recent study in 27 countries belonging to the European Union (EU) indicates that the economic costs of lung cancer for 2009 were €18.8 bn and the biggest contributor in economic productivity (Edge et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of lung cancer incidence is illustrated by the stratified nature of its biology and geno-environmental determinants (Minagawa et al, 2007;Tesfaye et al, 2007) that show both inter-and intra-country variations. The Globocan 2012 report shows marked inter-country incidence differences that are compounded by intra-country differences across regions, ethnic groups (WHO-IARC, 2014;Lortet-Tieulent et al, 2014), gender (Islami et al, 2015), a long latency period (30 years) and the degree of inhalation (Farnsworth et al, 2004).…”
Section: Introductionmentioning
confidence: 99%